APPLICATION OF THE PRINCIPLE OF VOLUNTARINESS IN MARITAL PROPERTY DECISIONS - Tri Zulfianti, Sintia; Ani Yumarni; Suprijatna, Dadang; Rumatiga, Hidayat (Transnational Business Law Journal, 2023)
Marital Property Assests or what is usually called ‘gono-gini; harta bersama’ is property acquired or obtained by a husband and wife together while they are in a marriage bond. The concept of shared prices or what is usually called gono-gini property comes from customs that continue to develop and are supported by positive law or Islamic law in Indonesia. Mediation is a peace institution in the Court which brings benefits to the Judges and the parties, there is good faith of the principals (husband and wife) in the process of resolving divorce cases, it is not uncommon for ego attitudes to be more dominantly put forward by each party. Mediation has a voluntary principle, each conflicting party comes to mediation of their own free will and willingness and there is no coercion or pressure from other parties or outside parties. This principle of voluntarism is built on the basis that people will be willing to work together to find a way out of their disputes, if they come to the negotiation place of their own choice.